An analysis of reading abilities in children with autism spectrum disorders. (March 2018) - Nally, Amanda; Healy, Olive; Holloway, Jennifer; Lydon, Helena
Highlights: Severe reading deficits are present in children with ASD. Reading deficits are present from an early age (below 6 years). Some relative proficiencies in reading include word reading (below 6 years) and reading rate (6 years and above). Autism symptomology is negatively correlated with word reading and non-word reading. Autism severity symptomatology is predictive of language scores with greater severity predicting greater reading deficits. Abstract: Background: This study examined the reading performance of a nationally representative sample of 110 children with autism spectrum disorder (ASD). Method: The sample was divided into two groups by age; 3:10–5:10 years (Group 1) and 6:00–17:3 years (Group 2). Core reading components were assessed across both groups, which included: word reading, comprehension, phonological awareness, phonemic awareness, reading rate, vocabulary, accuracy and non-word reading. Results: The data demonstrated impaired reading skills across reading components in both groups, with the exception of word reading pre-requisites for Group 1 and reading rate for Group 2. An analysis of the full sample found that many participants performed within the lowest possible range on standardized tests (standard score ≤55) in particular, comprehension (82%) and phonemic awareness (62%). Language abilities and autism symptomatology severity were assessed for relationships with reading outcomes. The largest relationships were in autism severity and vocabulary and multiple regression analyses indicated that autism severity was predictive of language scores suggesting that individuals presenting with more severe symptoms of autism demonstrated the most reading deficits. Conclusion: These findings highlight the severe reading deficits present in this population and the need for reading assessments as well as the design of highly individualized reading interventions.